GELIAT PEREMPUAN DESA SEPAT KABUPATEN SRAGEN GELORAKAN PROTOKOL KESEHATAN SAMPAI MANCA NEGARA - Sritami Santi Hatmini; Setyasih Harini (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2022)
The Covid-19 pandemic is an unexpected challenge for society. Family resilience is at stake but not the responsibility of men as the head of the family alone. Women during pandemics actually have a very big role to help maintain the integrity of the family both physically, spiritually, and economically. Women get dual roles not only focusing on domestic affairs but instead out of their "nest" to help the husband keep the kitchen smoke burning. For this reason, creativity and innovation enable women to be able to face the challenges and problems that arise as a result of the Covid-19 pandemic. This paper explains the role of women who entrepreneurship make handicrafts with unique character in order to have economic value while helping the government in the socialization of health protokols. Qualitative is used in this study to understand social phenomena in the natural specific context of the actions, speeches, and products as well as the perceptions of the research subjects. Data is obtained through library searching, interview, and documentation. The results showed that the economic success of the family is not only determined by men. Women who are creative by developing talent are able to maintain the economy of the family and society. This has been done by the women of Sepat Village, Masaran District of Sragen Regency who are able to sell their handicrafts abroad. The handicrafts of these women are not only of economic value but also play but also as a tool to further introduce Indonesia in foreign countries.